2016
DOI: 10.1002/ajim.22671
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of disinfectant use among nurses in U.S. healthcare facilities

Abstract: Background Disinfectant use among healthcare workers has been associated with respiratory disorders, especially asthma. We aimed to describe disinfectants used by U.S. nurses, and to investigate qualitative and quantitative differences according to workplace characteristics and region. Methods Disinfectant use was assessed by questionnaire in 8,851 nurses. Hospital characteristics were obtained from the American Hospital Association database. Results Working in a hospital was associated with higher disinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although not conclusive, both of these findings help to explain the predominance of S. aureus on different surfaces and are of particular importance within hospital settings where bleach is commonly used as a disinfectant 62-64 .…”
Section: Discussionmentioning
confidence: 96%
“…Although not conclusive, both of these findings help to explain the predominance of S. aureus on different surfaces and are of particular importance within hospital settings where bleach is commonly used as a disinfectant 62-64 .…”
Section: Discussionmentioning
confidence: 96%
“…However, chlorhexidine and povidone iodine are currently the agents the most commonly used for surgical hand/arm antisepsis [7]. Moreover, in a survey of a sample of the hospitals where NHSII nurses work, a chlorhexidine solution was used for surgical hand/arm antisepsis in 7 out of 8 hospitals surveyed [13]. Chlorhexidine is a skin sensitizer [6], and cases of occupational asthma or occupational airway allergy due to chlorhexidine have been reported in nurses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other disinfectants frequently used included hypochlorite bleach and hydrogen peroxide. Consistently, in a large study of US nurses,25 participants working in a hospital reported using mostly alcohol, hypochlorite bleach and quats (41%, 24% and 15%). In the same population, nurses were classified as highly exposed to alcohol, hypochlorite bleach or quats by a JTEM (41%, 34% and 48%) 24.…”
Section: Discussionmentioning
confidence: 61%